Artificial intelligence in assessment and formative feedback in higher education in Cape Verde - Pires, Djamila; F. Gonçalves, Bruno; Mesquita, Elza (Aprender, 2025)
This article analyzes the perceptions of higher education students in Cape Verde regarding the use of Artificial Intelligence (AI) in assessment and formative feedback processes. The study adopted a mixed, exploratory, and descriptive approach, combining online questionnaires to collect quantitative and qualitative data. The sample consisted of 86 undergraduate students from two Cape Verdean universities, with the questionnaire validated by experts and approved by the ethics committee of the Polytechnic Institute of Bragança. The results indicate that 44.7% of students believe that AI can make assessments fairer and more efficient, while 40.7% express doubts, and 15.1% do not believe in this possibility. Regarding automated feedback, the main benefits identified were speed of response (60.5%), personalization according to individual needs (50%), and data-based objectivity (44.2%), followed by continuous feedback (36%), resource suggestions (34.9%), and encouragement of self-assessment (31.4%). Qualitative analysis of open-ended responses complemented these results, highlighting perceptions about pedagogical interaction, trust in technology, and potential limitations. It is concluded that the integration of AI into assessment and formative feedback offers significant benefits for learning, but must be guided by ethical and pedagogical principles, ensuring that technology complements, rather than replaces, the role of the teacher.